Analisis dan Perbandingan Tools Forensik menggunakan Metode NIST dalam Penanganan Kasus Kejahatan Siber - Yuladi, Achmad Iqbal; Indrayani, Rini (LPPM STT Terpadu Nurul Fikri, 2023)
Cybercrime cases in Indonesia have increased yearly; during the COVID-19 pandemic as it is now, people rely on the internet to carry out daily activities such as teaching and learning activities, buying and selling online, working from home, etc. Therefore, cybercrime cases in Indonesia have increased. One of the most common examples is Cyberbullying cases on various social media networks with mobile platforms, one of which is WhatsApp Messenger. This study will analyze and compare the results of the MOBILedit Forensic Express and Magnet Axiom tools using the National Institute of Standards and Technology (NIST) method. This method can facilitate the investigation process in the case scenarios in this research. Researchers will also compare the results of the two tools used in this forensic process. The results of this study using the National Institute of Standards and Technology (NIST) method on the WhatsApp apps showed the Magnet Axiom tools were slightly superior with an accuracy of 82,8% compared to MOBILedit Forensics Express 72,7% in the condition that the object was not rooted.